Modulate Organic-Metal Oxide Heterojunction via [1,6] Azafulleroid for Highly Efficient Organic Solar Cells - Li, Chang-Zhi; Huang, Jiang; Ju, Huanxin; Zang, Yue; Zhang, Jianyuan; Zhu, Junfa; Chen, Hongzheng; Jen, Alex K.-Y. (Advanced materials (Weinheim), 2016)
By creating an effective π‐orbital hybridization between the fullerene cage and the aromatic anchor (addend), the azafulleroid interfacial modifiers exhibit enhanced electronic coupling to the underneath metal oxides. High power conversion efficiency of 10.3% can be achieved in organic solar cells using open‐cage phenyl C61 butyric acid methyl ester (PCBM)‐modified zinc oxide layer.